2023
DOI: 10.1039/d2en01040b
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum-based nanomaterials suppress bacterial wilt in tomato: importance of particle morphology and dissolution profiles

Abstract: Loss of crop yield to pathogen damage seriously threatens efforts to achieve global food security. In the present work, lanthanum (La) based nanomaterials (NMs) with different morphologies and compositions, including...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…For instance, Wang et al found that the critical component of the biosynthetic pathway of SA (e.g., cinnamic acid and p-coumaric acid) was significantly increased by spraying 100 mg L −1 lanthanum-based nanomaterials. 47 Moreover, nanochitosan carriers can protect SA from the interference of external environments, and thus in turn increased the SA accumulation in plant leaves. 13 In addition, we also found that the SCN100 treatment remarkably increased the maize leaf JA content by 541.9% and 19.1% in the presence and absence of S. frugiperda, respectively (Fig.…”
Section: Effect Of Scns On Maize Leaf Phytohormonesmentioning
confidence: 99%
“…For instance, Wang et al found that the critical component of the biosynthetic pathway of SA (e.g., cinnamic acid and p-coumaric acid) was significantly increased by spraying 100 mg L −1 lanthanum-based nanomaterials. 47 Moreover, nanochitosan carriers can protect SA from the interference of external environments, and thus in turn increased the SA accumulation in plant leaves. 13 In addition, we also found that the SCN100 treatment remarkably increased the maize leaf JA content by 541.9% and 19.1% in the presence and absence of S. frugiperda, respectively (Fig.…”
Section: Effect Of Scns On Maize Leaf Phytohormonesmentioning
confidence: 99%